Using a MOOC Format for a Precalculus Course. Issue 6 (2nd July 2016) - Townsley, Lisa
Abstract: We describe recent attempts by the University System of Georgia to develop and pilot a system-wide online Precalculus course for credit. The course was based on full online delivery, using an emporium model for learning. We experienced moderate success with the course, with a completion rate of 61–76% compared with the 4–7% for Massive Open Online Courses reported by studies in the literature. Persistence by students, as measured by logins and content viewed, correlated to student success. Based on student surveys, there is a significant disconnect between student perception of their learning and their performance in the course. We experienced several technical challenges with the course platform and responded to student requests for more video support of the text.